Adaptasi Psikososial Pasien Hemodialisis Terhadap Perubahan Gaya Hidup : Literature Review Psychosocial Adaptation Of Hemodialysis Patients To Lifestyle Changes : Literature Review - Bagus Yudantoro; Mam’nuah; Wantonoro (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Patients with end-stage chronic kidney disease undergoing hemodialysis experience complex lifestyle changes, including fluid and dietary restrictions, dependence on therapy, fatigue, changes in social roles, and psychological distress that affect psychosocial adaptation and quality of life. This literature review aimed to examine the factors influencing psychosocial adaptation among hemodialysis patients and their implications for nursing practice. The review was conducted using PubMed, Scopus, ScienceDirect, ProQuest, MDPI, and BMC databases with keywords related to hemodialysis and psychosocial adaptation. Inclusion criteria were full-text articles published between 2020–2025 in English or Indonesian that discussed psychosocial aspects of hemodialysis patients. Of 326 identified articles, 11 studies were analyzed using a narrative-thematic approach. The findings identified five major themes: illness acceptance, depression and anxiety, social support, burden of physical symptoms, and coping strategies and cultural values. Illness acceptance and social support positively contributed to psychosocial adaptation, whereas depression, anxiety, and physical symptom burden negatively affected patients’ quality of life. Overall, psychosocial adaptation in hemodialysis patients is influenced by psychological, social, physical, and cultural factors. Therefore, nurses should perform routine psychological screening, provide self-management education, strengthen family support, and facilitate adaptive coping strategies to improve patient outcomes.Top of Form